2023
DOI: 10.1186/s12967-023-04333-x
|View full text |Cite
|
Sign up to set email alerts
|

CHSY3 promotes proliferation and migration in gastric cancer and is associated with immune infiltration

Abstract: Background The glycosyltransferase CHSY3 is a CHSY family member, yet its importance in the context of gastric cancer development remains incompletely understood. The present study was thus developed to explore the mechanistic importance of CHSY3 as a regulator of gastric cancer. Methods Expression of CHSY3 was verified by TCGA, GEO and HPA databases. Kaplan–Meier curve, ROC, univariate cox, multivariate cox, and nomogram models were used to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…High CHSY2 expression has been associated with the occurrence of choriocarcinoma and its metastasis ( 23 ). However, only recent reports have shown that CHSY3 expression is associated with the development and metastasis of gastric cancer ( 24 , 25 ). Like in their study, in which we evaluated the expression of CHSY3 via TIMER, TCGA and other databases, we found that CHSY3 was abnormally highly expressed in a variety of cancers, and compared with paraneoplastic tissues, CHSY3 was more highly expressed in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…High CHSY2 expression has been associated with the occurrence of choriocarcinoma and its metastasis ( 23 ). However, only recent reports have shown that CHSY3 expression is associated with the development and metastasis of gastric cancer ( 24 , 25 ). Like in their study, in which we evaluated the expression of CHSY3 via TIMER, TCGA and other databases, we found that CHSY3 was abnormally highly expressed in a variety of cancers, and compared with paraneoplastic tissues, CHSY3 was more highly expressed in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To predict survival probabilities at 1 year, 3 years, and 5 years, we used the R package “rms” to visualize the relationship between overall survival rates and predictive factors, including age, gender, stage, T stage, M stage, N stage, and the DDX52 gene. In the column chart, a point proportion scale was employed to assign points to each parameter, with these being summed for an overall point score 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The GSE15605 and GSE114445 datasets were retrieved fro m the Gene Expression Omnibus database (GEO, https://www.ncbi.nlm.nih.gov/g eo/). KEGG, GO, and GSEA analyses were performed using appropriate R soft ware package (40), following established methods.…”
Section: Bioinformatics Analysismentioning
confidence: 99%